Priority Directions of Fighting Against Threats to Nationalism in Providing International Harmony and Solidarity - Kholmatov Uchkunjon Khamidullaevich (International Journal of Formal Education, 2024)
this article analyzes the priority directions of combating threats to nationalism in ensuring inter-ethnic harmony and solidarity, socio-philosophical research of inter-ethnic harmony and solidarity in the context of informational and cultural struggles.